Nasehat Biblikal yang Menjadi Norma Seorang Pemimpin Jemaat: Sebuah Kajian Teologis-Etis Berdasarkan Titus 1:5-9 - Jarangga, Gadrin George Roberth; Waani, Marciano Antaricksawan; Situmorang, Jonar (Integritas: Jurnal Teologi, 2024)
This theological-ethical study aims to explore the biblical advice that serves as norms for a church leader, with a focus on Titus 1:5-9. The research method employed in this study is descriptive analysis technique. This approach focuses on interpreting the meanings given by individuals or groups to specific experiences or situations. In qualitative research, researchers are more interested in understanding the social, cultural, and psychological contexts of the phenomena under investigation. The findings of the study indicate that these norms provide clear guidelines for the character, qualifications, and responsibilities of a church leader. The advice includes criteria necessary for a leader, such as moral integrity, family commitment, and personal piety. Furthermore, these norms emphasize the importance of leadership that is strong, wise, and based on biblical teachings. This study also highlights the flexibility in applying these norms according to the context and needs of specific churches.